Pemanfaatan E-Learning Quipper School oleh Guru dan Siswa untuk Optimalisasi Pembelajaran di MAN 1 Ponorogo - Ghulam Asrofi Buntoro; Dwiyono Ariyadi; Indah Puji Astuti (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2018)
The role of Science and Technology (IT) is huge nowadays. The role covers many fields. One of them is education. MAN 1 Ponorogo is one of the schools in Ponorogo district that has extra computer-based activities for a minimum level of diploma 1. It affects the increase in lesson hours. Therefore, to maximize face-to-face required innovative learning media. One such example is e-learning. E-learning is also expected to be used actively by students. E-learning is a learning system that utilizes communication and information technology (ICT) in the learning process between teachers and learners. The purpose of this program is to socialize e-learning quipper to teachers and students in MAN 1 Ponorogo to optimize learning and teaching activities (KBM). In the event, seventeen teachers were present and active. Eleven teachers strongly agree with e-learning quipper because it is easy and useful. As of the 24 students present and active, 2 students still have difficulty in using e-learning quipper. Thus, more than 95% of participants can use the e-learning quipper.